Predictions for 2025: Artificial Intelligence in Modern Drug Development, Quantum Proof Encryption, and Health Data Monetization - Vasiliu-Feltes MD, EMBA, Ingrid; Hinkel, MSc, CHW, FRSA, Jennifer; Kubassova, PhD, Olga (Blockchain in Healthcare Today, 2024)
We are witnessing an unprecedented convergence of scientific discoveries, technology innovations, exponential adoption of technology and remarkable population demographic shifts towards a digitally native society. The Noble Prizes in medicine, chemistry, physics awarded this year further validated the profound impact of technology on healthcare and life sciences. For 2025-designated by the United Nations as The Year of Quantum Technology, we can envision further technology-driven innovations in all domains, triggering the transition to a novel health ecosystem. The role of AI in modern drug development, the demand for quantum-proof encryption, and the opportunities of blockchain in health data monetization are all trends can be disruptive for pharma, healthcare and healthcare finance.